The role of COD/N ratio on the start-up performance and microbial mechanism of an upflow microaerobic reactor treating piggery wastewater. (1st July 2018) - Meng, Jia; Li, Jiuling; Li, Jianzheng; Astals, Sergi; Nan, Jun; Deng, Kaiwen; Antwi, Philip; Xu, Pianpian
Abstract: This study investigated the role of COD/N ratio on the start-up and performance of an upflow microaerobic sludge reactor (UMSR) treating piggery wastewater at 0.5 mgO2 /L. At high COD/N ratio (6.24 and 4.52), results showed that the competition for oxygen between ammonia-oxidizing bacteria, nitrite-oxidizing bacteria and heterotrophic bacteria limited the removal of nitrogen. Nitrogen removal efficiency was below 40% in both scenarios. Decreasing the influent COD/N ratio to 0.88 allowed achieving high removal efficiencies for COD (∼75%) and nitrogen (∼85%) due to the lower oxygen consumption for COD mineralization. Molecular biology techniques showed that nitrogen conversion at a COD/N ratio 0.88 was dominated by the anammox pathway and that Candidatus Brocadia sp. was the most important anammox bacteria in the reactor with a relative abundance of 58.5% among the anammox bacteria. Molecular techniques also showed that Nitrosomonas spp. was the major ammonia-oxidiser bacteria (relative abundance of 86.3%) and that denitrification via NO3 − and NO2 − also contributed to remove nitrogen from the system. Graphical abstract: Image 1 Highlights: An upflow microaerobic sludge reactor was started up to treat piggery wastewater. COD/N ratio had a remarkable influence on the nitrogen removal. Competition for oxygen among oxygen-consuming bacteria limited the nitrogen removal. A nitrogen removal up to 85% was achieved with a low COD/N ratio of 0.88. Molecular biology revealed anammox as the dominated nitrogen removal pathway.